Instructional Design For Students With Visual Impairments In English Learning - Farani, Rizki; Aryanti, Widya (English Education Department, Universitas Islam Indonesia, 2011)
Mastering English has become one important skill for students in higher education, especially in university level. As the impact, every university provides English program for students in the faculty or language center. However, not every student can master English fast, for example: students with visual impairments. Students with visual impairment are a group of students who have visual problem; either it is low vision or blind. Students with visual impairment need different approach in learning English. This condition motivates lectures to adapt specific instructional design to support classroom activities. There are 4 important components in designing instructional design for students with visual impairment, such as students' characteristics, learning objective, method and assessment. The design should be adapted to fully support their inclusion in the classroom. By designing instructional design for students with visual impairments, it is expected that they will be able to comprehend the material and to increase their motivation in learning English. This paper aimed to understand appropriate instructional design for students with visual impairment. This paper also provides study cases in Inclusion English Class at university level where students with visual impairment and sighted students study at the same classroom. By discussing this issue, it is expected that every lecture recognize basic characteristics of students with visual impairment and choose the appropriate instructional design to accommodate all character of students.